The role of the astrocytic marker S100B in HIV-associated neurocognitive disorders - Groenewald, Engelina (Department of Psychiatry and Mental Health, 2020)
There are as yet no ideal biomarkers of HIV-associated neurocognitive disorders. As astrocytosis is a feature of HIV encephalitis, the marker S100β may hold promise as a biomarker of HAND. We explored associations between S100β and neurocognition in individuals with HIV in Cape Town, South Africa, before and after antiretroviral therapy (ART) was initiated. The S100β levels in the cerebrospinal fluid (CSF) of forty-six participants with HIV, but not yet on antiretroviral therapy, was quantified using an enzyme-linked immunoassay (ELISA). A battery of cognitive tests was performed and the global deficit score (GDS) was calculated. In twenty of these patients, the S100β analysis and the cognitive tests were repeated approximately six months after the initiation of ART. There was no significant association between cerebrospinal fluid S100β and GDS at baseline (r= -0.070; p= 0.66) or after six months of ART (r= 0.16; p= 0.52). Cerebrospinal fluid S100β levels at baseline did not predict a change in neurocognition on ART (B(SE) = 0.001, (0.001), β=0.025, p=0.85). S100β in the cerebrospinal fluid may not adequately reflect neurocognitive impairment in individuals with HIV. Our results further demonstrate that CSF S100β levels are not affected by ART, indicating persistent neuroinflammation.